1984
DOI: 10.1002/ange.19840960221
|View full text |Cite
|
Sign up to set email alerts
|

Ein Biphenylenylendiporphyrin: Zwei cofacial angeordnete Porphyrine mit Biphenylenbrücke

Abstract: Et,N)2Fe&16. Die pli%ttchenfUrmigen, schwarzen Kristalle sind an der Luft mehrere Tage haltbar. [4] Eine ahnliche Struktur wie die FesSs-Einheit haben die Ag.,M2S6-G~ppen (M=Mo. W) in den Verbindungen (R3P)&,M2S8: A. MUller, E. Diemann, R Jostes, H. BUgge, Angew. Chem. 93 (1981) 957; Angew. Chem. fnt. Ed. Engf. 20 (1981) 934 (zit. Lit.): J. K. Stalick, A. R. Siedle, A. D. Mighell, C. R Hubbard, J. Am. Chem. SOC. IOI (1979) 2908. [5] Vgl. East Lansing, MI 48824 (USA) Wir danken M . Shih fur die Herstellung der … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
11
0

Year Published

1987
1987
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…Materials: H 2 P, H 4 DPS, [12] H 4 DPX, [39] H 4 DPB, [61] and their metalated derivatives [12,34,39,41,62] were synthesized by using methods reported in the literature. Unless otherwise stated, all reagents and solvents were used as received.…”
Section: Methodsmentioning
confidence: 99%
“…Materials: H 2 P, H 4 DPS, [12] H 4 DPX, [39] H 4 DPB, [61] and their metalated derivatives [12,34,39,41,62] were synthesized by using methods reported in the literature. Unless otherwise stated, all reagents and solvents were used as received.…”
Section: Methodsmentioning
confidence: 99%
“…

Porphyrins are widely used for functional molecular systems based on their excellent photophysical and redox properties. [2,3] Cofacial porphyrin dimers can be readily constructed by linking two porphyrin rings by covalent, [4][5][6][7][8][9][10][11][12] hydrogen, [13] or coordination bonds. [2,3] Cofacial porphyrin dimers can be readily constructed by linking two porphyrin rings by covalent, [4][5][6][7][8][9][10][11][12] hydrogen, [13] or coordination bonds.

…”
mentioning
confidence: 99%
“…The solvent was chosen for the good solubility of both 1 and the complexes. ESI-MS measurements of the sample gave a set of signals assigned to the porphyrin dimer [Ag 4 The 1 H NMR spectrum showed that 1 adopted a C 4 symmetry in the complex.…”
mentioning
confidence: 99%
See 2 more Smart Citations